Virome Characterization of a Collection of S. sclerotiorum from Australia - Mu, Fan; Xie, Jiatao; Cheng, Shufen; You, Ming Pei; Barbetti, Martin J.; Jia, Jichun; Wang, Qianqian; Cheng, Jiasen; Fu, Yanping; Chen, Tao; Jiang, Daohong (Frontiers in Microbiology, 2018)
Sclerotinia sclerotiorum is a devastating plant pathogen that attacks numerous economically important broad acre and vegetable crops worldwide. Mycoviruses are widespread viruses that infect fungi, including S. sclerotiorum. As there were no previous reports of the presence of mycoviruses in this pathogen in Australia, studies were undertaken using RNA_Seq analysis to determine the diversity of mycoviruses in 84 Australian S. sclerotiorum isolates collected from various hosts. After RNA sequences were subjected to BLASTp analysis using NCBI database, 285 contigs representing partial or complete genomes of 57 mycoviruses were obtained, and thirty four of these (59.6%) were novel viruses. These 57 viruses were grouped into 10 distinct lineages, namely Endornaviridae (four novel mycoviruses), Genomoviridae (isolate of SsHADV-1), Hypoviridae (two novel mycoviruses), Mononegavirales (four novel mycovirusess), Narnaviridae (10 novel mycoviruses ), Partitiviridae (two novel mycoviruses), Ourmiavirus (two novel mycovirus), Tombusviridae (two novel mycoviruses), Totiviridae (one novel mycovirus), Tymovirales (five novel mycoviruses) and two non-classified mycoviruses lineages (one Botrytis porri RNA virus 1, one distantly related to Aspergillus fumigatus tetramycovirus-1). Twenty-five mitoviruses were determined and mitoviruses were dominant in the isolates tested. This is not only the first study to show existence of mycoviruses in S. sclerotiorum in Australia, but highlights how they are widespread and that many novel mycoviruses occur there. Further characterization of these mycoviruses is warranted, both in terms of exploring these novel mycoviruses for innovative biocontrol of Sclerotinia diseases and in enhancing our overall knowledge on viral diversity, taxonomy, ecology and evolution.